2020
DOI: 10.1097/01.asw.0000658592.51430.ea
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cytotoxicity of Various Hand Disinfectants and Ozonated Water to Human Keratinocytes in a Cultured Epidermal Model

Abstract: OBJECTIVE To evaluate the cytotoxicity of various hand disinfectants and ozonated water to human keratinocytes using a cultured epidermal model. DESIGN Using a test protocol from the Organization for Economic Co-operation and Development, investigators applied hand disinfectants containing either 83% ethanol, 0.2% benzalkonium chloride, 0.5% povidone-iodine, 1% chlorhexidine, 1% chlorhexidine ethanol, or ozonated water to a cultured human epidermal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…However, these disinfectants have been shown to cause skin irritation, and as handwashing measures have now been strengthened, healthcare professionals were reported to exhibit increased skin irritation (Erdem et al, 2020 ; Guertler et al, 2020 ; Lan et al, 2020 ). Recent studies have shown that OW is less irritating to the skin than traditional disinfectants, raising interest in OW as an alternative handwashing treatment (Breidablik et al, 2019 ; Kashiwazaki et al, 2020 ). Likewise, OG is also less irritating to the skin and has a longer ozone half-life than OW (Fukui et al, 2015 ; Wang et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these disinfectants have been shown to cause skin irritation, and as handwashing measures have now been strengthened, healthcare professionals were reported to exhibit increased skin irritation (Erdem et al, 2020 ; Guertler et al, 2020 ; Lan et al, 2020 ). Recent studies have shown that OW is less irritating to the skin than traditional disinfectants, raising interest in OW as an alternative handwashing treatment (Breidablik et al, 2019 ; Kashiwazaki et al, 2020 ). Likewise, OG is also less irritating to the skin and has a longer ozone half-life than OW (Fukui et al, 2015 ; Wang et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though EtOH is more stable than OW and SAEW, its skin irritation and the existence of alcohol-intolerant people are disadvantages. Previous reports suggest that the skin irritancy of OW is lower than that of EtOH [ 15 , 16 ]. In contrast, since SAEW is also considered to be safe and has low irritation to skin and mucous membranes, it has been proposed for use as a disinfectant for normal and wounded skin [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Routine disinfection practices have evolved during the ongoing pandemic, and several sectors have required enhanced disinfection of contact surfaces. SARS-CoV-2 has shown to persist on surfaces up to 72 hours (van Doremalen et al 2020), whereas other coronaviruses have persisted up to 9 days on surfaces (Kampf et al 2020). While surface contact is not considered to be the primary SARS-CoV-2 transmission route, it should not be entirely ignored.…”
Section: Treatment Of Surfacesmentioning
confidence: 99%
“…Despite issues associated with respiratory exposure to ozone, aqueous ozone does not damage human skin cells, as its cellular degradation action is selective to microbial cells (Gupta and Mansi 2012). When experimentally compared with various hand disinfectants, ozonated water resulted in minimal cytotoxicity to the human keratinocytes (Kashiwazaki et al 2020). Aqueous ozone has been considered as an alternative to chlorine-based disinfectants in food processing (Rice, Graham, and Lowe 2002), and has great potential of improving disinfection toward COVID-19 control in various sectors.…”
Section: Treatment Of Surfacesmentioning
confidence: 99%
See 1 more Smart Citation